2019
DOI: 10.3390/jmse7100333
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of a Winglet-Propeller Using an LES Model

Abstract: The generation of tip vortex cavitation (TVC) is a common phenomenon in marine propellers. Therefore, it is important to find a way for the effective suppression of TVC. Based on the enlightenment of bionics, a propeller with winglets was numerically investigated by using a large eddy simulation (LES) model and the commercial software STAR-CCM+. Various variables, such as mesh size, number of prism layers, vapor properties and time step, were analyzed using the benchmark MAU5-80 propeller. The open water chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…In addition, for motor blades, inspired by bionics, 160 Zhu and Gao utilized a winged propeller to suppress the generation of tip vortex cavitation (TVC). 45 Also, the simulation results showed that the winglet propeller significantly weakened the strength of the blade tip vortex wake and had a significant effect. Moreover, inspired by the shark skin effect, Büttner and Schulz prepared a riblet structure surface with a fluid wall friction reduction of 4.9%.…”
Section: Applicationsmentioning
confidence: 95%
“…In addition, for motor blades, inspired by bionics, 160 Zhu and Gao utilized a winged propeller to suppress the generation of tip vortex cavitation (TVC). 45 Also, the simulation results showed that the winglet propeller significantly weakened the strength of the blade tip vortex wake and had a significant effect. Moreover, inspired by the shark skin effect, Büttner and Schulz prepared a riblet structure surface with a fluid wall friction reduction of 4.9%.…”
Section: Applicationsmentioning
confidence: 95%
“…However, the LES studies currently available in the literature typically rely on computational grids consisting of points, similar to those for the DES computations reported above, and are usually targeted at analysing the process of instability of the wake system of marine propellers and the cavitation phenomena occurring within the large coherent structures they shed (Liefvendahl 2010; Liefvendahl, Felli & Troëng 2010; Asnaghi, Svennberg & Bensow 2018 a , b , 2020 a ; Hu et al. 2019 a ; Zhu & Gao 2019; Ahmed, Croaker & Doolan 2020; Asnaghi et al. 2020 b ; Long et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the limitations in terms of both grid resolution and computational technique, negatively affecting the simulation of the wake flow and resulting in the quick diffusion of the wake structures. An exception in this field is the work reported by Zhu & Gao (2019). However, they adopted LES on a grid consisting of only 11 million points, similar to those typical of lower-fidelity, RANS computations and not well suited to eddy-resolving simulations.…”
Section: Introductionmentioning
confidence: 99%